2011
DOI: 10.1148/radiol.11101664
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Acute Renal Transplant Dysfunction with Low-Dose Three-dimensional MR Renography

Abstract: Low-dose MR renography analyzed by using a multicompartmental tracer kinetic renal model may help to differentiate noninvasively between acute rejection and ATN after kidney transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…A significantly higher RPF in the cortex compared to the medulla is expected for the more vascularized cortex. A three-compartment model was chosen, rather than simpler models (Patlak plot, whole-kidney or dual compartment) because it permits separation of cortical and medullary function, and was previously shown to provide information on renal tubular function, and to differentiate between acute rejection and acute tubular necrosis of renal allografts (27). Like previous investigators, we found that the model–derived GFR was systematically lower than serum eGFR (2).…”
Section: Discussionmentioning
confidence: 99%
“…A significantly higher RPF in the cortex compared to the medulla is expected for the more vascularized cortex. A three-compartment model was chosen, rather than simpler models (Patlak plot, whole-kidney or dual compartment) because it permits separation of cortical and medullary function, and was previously shown to provide information on renal tubular function, and to differentiate between acute rejection and acute tubular necrosis of renal allografts (27). Like previous investigators, we found that the model–derived GFR was systematically lower than serum eGFR (2).…”
Section: Discussionmentioning
confidence: 99%
“…New advances in the quick acquisition of dynamic, postcontrast, time-resolved images and delayed postcontrast excretion urographic images have introduced comprehensive MR nephro-urography and renography, enabling quantitative measurements of renal function, including individual kidney GFR and renal blood flow, in postprocessing. More recently, multicompartm ental kinetic modeling was applied in the postprocessing of MR renography, generating separate parameters for the vascular and tubular compartments [21][22][23][24] . This model benefits from the use of the lowest possible concentration of gadolinium-chelate [3] .…”
Section: Mr Nephro-urography/renographymentioning
confidence: 99%
“…To assess intrinsic causes of renal dysfunction, such as AR and ATN, Yamamoto et al [24] performed quantitative low-dose 3D MR renography on sixty patients with transplanted kidneys. The GFR and the mean transit time (MTT) of the tracer were calculated using a multicompartment renal model.…”
Section: Mr Nephro-urography/renographymentioning
confidence: 99%
“…Another problem is the potential nephrotoxicity of the gadolinium which is generally used as contrast agent in a chelated form. Using low dose three dimensional magnetic resonance renography, the mean transit time of the tracer for the different compartment of the kidney (vascular, tubular and collecting system) was measured different in normal kidneys, transplanted kidneys with acute tubular necrosis and transplanted kidney with acute rejection (Yamamoto et al, 2011) indicating that a multicompartimental tracer kinetic renal model may help to differentiate acute rejection from acute tubular necrosis in transplanted kidney.…”
Section: Magnetic Resonance In Vivo 31 Mrimentioning
confidence: 99%